Development of Watercolor Paint Made from Plant Pigments - Mate, Jemuel M.; Monta, Dianne Ivy M.; Pedragoza, Claire J.; Nazareno, Althea Sheen A.; Merlin, Menandro M.; Mascareñas, Mario T.; Pascua, Ma. Lorraine M.; Historillo, Jan Fern; Adling, Nikka Mae J.; Rocha, Aynah N.; Mantaring, Nicko N.; Aldovino, Andrea E.; et al. (International Journal of Research in Interdisciplinary Studies, 2026)
This study focused on the development and evaluation of watercolor samples derived from alternative materials. It aimed to identify the physical characteristics of the developed watercolors, including color temperature (warm or cool) and lightfastness (fugitive or non-fugitive). The study also evaluated the quality of the samples using a four-point Likert scale, focusing on granulation, staining, transparency, and pigment number, and sought to determine any significant differences between the developed samples and commercially available control samples. An experimental research design was employed, and data were gathered from artists, Drafting Technology students, and faculty members from the College of Industrial Technology. The results were analyzed using mean, standard deviation, and ANOVA (Analysis of Variance). Findings revealed that all red, yellow, and blue treatments exhibited cool shades, whereas control yellow samples showed warm tones. In terms of lightfastness, all developed colors were rated as semi-fugitive. For granulation, red treatments were rated as semi-granulating, while yellow and blue treatments were non-granulating. Regarding staining, RT50 red was classified as staining, and RT25 and RT75 as highly staining; yellow and blue treatments were also rated as highly staining. All color treatments were rated opaque in terms of transparency. As for pigment composition, RT50 was identified as containing triple pigments, while the others contained multiple pigments. ANOVA results showed significant differences between the developed and control samples. In red color samples, granulation, staining, and pigment number showed significant differences, while transparency did not. For yellow and blue samples, granulation and pigment number were also found to be significantly different, while staining and transparency were not. These findings suggest that the developed watercolor samples, despite being derived from alternative materials, exhibit characteristics and performance comparable to those of commercial watercolors, supporting their potential use in creative and technical applications.